KPK Authority to Investigate, Prosecute, and Prosecute Corruption Offences Connexity - Yuliansyah, Riski; Dahlan; M. Jafar (LAW & PASS: International Journal of Law, Public Administration and Social Studies, 2025)
The unclear legal arrangements in Chapter XI of the Criminal Procedure Code (KUHAP), particularly Article 89 to Article 94, have created legal uncertainty for the KPK in carrying out the functions of investigation and prosecution of koneksitas cases. This has resulted in weak coordination between the KPK and military institutions, which has an impact on suboptimal case handling and potential violations of the principle of justice. This research uses normative legal methods with regulatory, conceptual, and case study approaches. The results showed that Article 89 of KUHAP gives priority to the General Court in processing koneksitas cases, but does not explicitly regulate the KPK's authority. This lack of clarity has made it difficult for the KPK to form a joint team with the Military Oditur as stipulated in Article 89 paragraph (2) of KUHAP. This lack of legal certainty is a major obstacle in the effort to enforce a just and effective law.